Analysis of the Influence of Principal Policy on Improving the Quality of Islamic Education - Hendy Aldian; Ahmad Sulhan; Lukman Hakim (Program Studi Manajemen Pendidikan, 2024)
The aim of this research is to explain the influence of the principal's policy on the quality of Islamic education at SMA IT Yarsi Mataram. This research uses a quantitative type with an analytical design. The population of this study were all teachers and students of SMA IT Yarsi Mataram and the sample was 10 teachers and 15 students. The sampling technique used is random sampling. Data collection techniques through observation with questionnaire instruments for Islamic education policy and quality. The data analysis technique uses the t test and/or F test. The results of the research show that there is an influence of the principal's policy on the quality of Islamic education at SMA IT Yarsi Mataram as seen from the significant value obtained in the t test and F test of 0.000 which is smaller than 0.05. This means Ha is accepted and Ho is rejected. This shows that there is an influence of the principal's policy on improving the quality of Islamic education at SMA IT Yarsi Mataram. The better the policies decided by the school principal, the more the quality of Islamic education will improve. This research is a stimulus for school principals to consider all their policies because they will determine the quality of the school.